Why didn’t you resist? Situational influences on victim resistance during a rape - Chopin, Julien (International review of victimology, 2023)
The purpose of this study is to examine factors influencing victim resistance during rape. Specifically, this study aims to understand which factors impact victim resistance using a multivariate approach focused on situational aspects related to offender, victim, and crime context characteristics. The sample includes 2,017 rape cases where victims did not resist, resisted passively, resisted verbally, or resisted physically. The first step of this study uses bivariate analyses to examine the relationship between the different categories of victim resistance and offender, victim, and crime context characteristics. Second, we computed three sequential binomial regressions in order to better understand the impact of each variable in multivariate modeling. The findings suggest that victim resistance is impacted by three main dimensions: victims’ physical and psychological vulnerabilities, the mentalizing of victimization risk, and the analysis of offenders’ vulnerabilities and additional risks to the victim. Both theoretical and practical implications for victims as well as for various actors in the criminal justice system are discussed.